Gender Diversity: ESG terhadap kinerja keuangan - Julianda, Yuda; Venza Aditiya, Okta; Yuniarti, Rina; Adiansyah, Dicky (Accounting Study Program, Universitas Ciputra Surabaya, 2026)
The connection between financial outcomes and Environmental, Social, And Governance (ESG) is explored in this study, where gender diversity acts as a moderating influence within Indonesian manufacturing companies. This quantitative research employs a purposive sampling method for firms listed on the Indonesia Stock Exchange from 2020 to 2024, utilizing agency theory and stakeholder theory. Over a five-year period, 120 observation units were established from 24 companies that met the study's criteria out of 232 manufacturing firms. The data was processed through moderated regression analysis using the Eviews 12 software. The results indicate that ESG has a significant positive effect on the financial performance of manufacturing companies. Moreover, gender diversity notably enhances the connection between ESG efforts and financial outcomes, implying that having diverse leadership positively influences the impact of ESG practices on financial performance. In the Indonesian manufacturing industry, these insights incorporate gender diversity as a moderating element in the relationship between ESG and financial performance, providing a new theoretical perspective. The study's real-world implication suggests that manufacturing companies should adopt ESG practices and enhance gender diversity in leadership roles to optimize financial performance and promote business sustainability in the long run.